2016
DOI: 10.31436/ijes.v4i2.115
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Belief on the Benefit of Collaboration in Lesson Study

Abstract: Lesson study is being actively implemented in many countries as one of the continuous professional development program for school teachers. Since collaboration is an important element of lesson study, it is deemed necessary to investigate teachers’ beliefs about collaboration in lesson study. Data were collected through both qualitative and quantitative methods, where teachers were surveyed via questionnaire, interviewed, observed and asked to keep a journal. Thirty-one teachers and a school administrator who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Clearly, this implied the critical situation of LS among MTEs in LS model 1. Most of them in this survey requested a typical model and reliable sources of LS because if teachers can “see the benefits of LS then they would be willing to allocate their time and energy to the practice” (Khalid et al , 2016). Therefore, in order to overcome this situation of LS model 1, revising LS guidelines, enhancing the LS system in those TTCs and providing LS experts or “knowledgeable other” in those TTCs become clear.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, this implied the critical situation of LS among MTEs in LS model 1. Most of them in this survey requested a typical model and reliable sources of LS because if teachers can “see the benefits of LS then they would be willing to allocate their time and energy to the practice” (Khalid et al , 2016). Therefore, in order to overcome this situation of LS model 1, revising LS guidelines, enhancing the LS system in those TTCs and providing LS experts or “knowledgeable other” in those TTCs become clear.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Lesson study (LS) is a model for teacher professional learning of both pre- and in-service teachers. It is “a long-term teacher-led professional learning approach.” Teachers try out the concept of learner-center to correspond new curriculum reform that emphasizes “mathematical thinking, reasoning, communication and problem-solving” (Khalid et al , 2016). LS changes teachers’ knowledge of mathematics and student thinking, pedagogy, sets a long-term goal, improves the process of collegial work and the task in the lesson (Lewis et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Staff members working together in a strong collaborative environment report more confidence, strong self-efficacy, better emotional and psychological well-being, and reduced worry in their primary duties ( Dehdary, 2017 ; Moolenaar et al., 2011 ; Shakenova, 2017 ). Senior and junior academic staff collaboration and support enhance subject knowledge, pedagogy, as well as research and community service skills ( Goddard et al., 2007 ; Khalid et al., 2016 ). Furthermore, researchers found that staff collaboration is crucial to professional reflection ( Jong et al., 2019 ), enhance productivity and effectiveness ( Ervin, 2011 ), share common beliefs, attitudes, ideas, and better alternatives to bring further improvements ( Jao and Mcdougall, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, Fernandez (2002) & Sumarni et al (2020 state that a Lesson study can be seen as an approach to improving learning. Lesson study has the advantage of creating collaboration between teachers in developing education, providing opportunities for teachers to solve learning problems together, and making teachers communicate closer (Khalid et al, 2016;Wood & Cajkler, 2018). Sucilestari & Arizona (2019) & Yalcin (2019 write that a Lesson study is a form of approach to improving the quality of learning carried out by teachers in a collaborative way.…”
Section:  Introductionmentioning
confidence: 99%